Evaluation The Use Of Facility Fishing Port Telaga Punggur Batam City - Hasanah, Liddiati; Zain, Jony; ', Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in October 2013 in Telaga Punggur Fishery Port Batam Riau Islands Province. The research was conducted using a survey method. The purpose of this research to know the level of utilization of the facility, knowing the problems in the implementation of activities, as well as the possibility of the development of facilities. Having done this research note dock facility utilization rate of 146.36%, the port pool of 956.07%, pool depth of 93.75%, amounting to 31.67% Coldstorage, ice plant by 90%. Issues contained in this fishing port include dernaga utilization rates, harbor expansive pool already exceeds capacity, coldstorage underutilized facilities, there are no fuel filling facilities, lack of completeness of the docking facility for heavy equipment repair damage to the fishing fleet and there is no safety on the outskirts of the shipyard in the form of ponds or Graving Dock. Under these conditions Telaga Punggur Fishery Port (Pt. SYS) for the future should be developed and should complete the required facilities.Keywords: Utilization of facilities, facilities, fishing port, Batam